2013
DOI: 10.1016/j.socec.2013.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Smokers, smoking deprivation, and time discounting

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…Ida and Goto determined that a higher individual rate is associated with a greater likelihood of smoking, abusing alcohol and gambling (Ida and Goto, 2009). Harrison et al, Scharff and Viscusi and Yamane et al confirmed that smokers discount utility from consumption at a higher rate than non-smokers (Harrison et al, 2010;Scharff and Viscusi, 2011;Yamane et al, 2013). Khwaja et al showed the orientation of smokers on the present moment (Khwaja et al, 2007).…”
Section: Determinants Of Fast-food Consumption and Individual Time Pr...mentioning
confidence: 98%
See 1 more Smart Citation
“…Ida and Goto determined that a higher individual rate is associated with a greater likelihood of smoking, abusing alcohol and gambling (Ida and Goto, 2009). Harrison et al, Scharff and Viscusi and Yamane et al confirmed that smokers discount utility from consumption at a higher rate than non-smokers (Harrison et al, 2010;Scharff and Viscusi, 2011;Yamane et al, 2013). Khwaja et al showed the orientation of smokers on the present moment (Khwaja et al, 2007).…”
Section: Determinants Of Fast-food Consumption and Individual Time Pr...mentioning
confidence: 98%
“…Harrison et al ., Scharff and Viscusi and Yamane et al . confirmed that smokers discount utility from consumption at a higher rate than non-smokers (Harrison et al ., 2010; Scharff and Viscusi, 2011; Yamane et al ., 2013). Khwaja et al .…”
Section: Determinants Of Fast-food Consumption and Individual Time Pr...mentioning
confidence: 99%